On the dynamics of the spring seasonal transition in the two hemispheric high-latitude stratosphere. Issue 1 (1st January 2019) - Wang, Tongmei; Zhang, Qiong; Hannachi, Abdel; Lin, Yihua; Hirooka, Toshihiko
Abstract: The seasonal transition is one of the main features of the atmospheric general circulation and is particularly manifest in the high-latitude stratosphere. To explore the dynamics of stratospheric seasonal transition in both hemispheres, the observational features of the annual cycle and seasonal transition in high-latitude stratosphere are investigated using the 38-year ERA-interim reanalysis. Climatological analysis shows that tropospheric planetary waves propagate to the stratosphere and affect significantly the winter-to-summer stratospheric seasonal transition over both hemispheres, but with a much stronger wave activity in austral spring than its boreal counterpart. The austral spring seasonal transition occurs first at the stratopause then propagates down to the lower stratosphere due to enhanced planetary wave breaking, weakening the westerlies. In boreal spring, the seasonal transition occurs simultaneously across the depth of the stratosphere, mainly due to the solar radiation and weaker planetary wave activity. Interannual variability analysis shows that the timing of stratospheric seasonal transition is closely linked to the intensity of upward propagation of planetary wave activity, i.e. the stronger the upward propagation of planetary wave activity in high-latitudes in spring the earlier the stratospheric seasonal transition. Transition indexes are defined and the probability distributions of the indexes show that there are two types of transition in both hemispheres: synchronous/asynchronous in the Northern Hemisphere (NH), and steep/moderate transitions in the Southern Hemisphere (SH). A composite analysis shows that before the transition, stronger wave activity leads to asynchronous rather than synchronous transition in the NH, which propagates downward from the stratopause. In the SH, a moderate rather than steep transition is obtained, which occurs earlier and takes longer to propagate from the upper to lower stratosphere.